Epidemiological profile of syphilis and the role od the Dentist (Research, Society and Development, 2020)
Introduction: Syphilis case have increased in Brazil. This disease is caused by the bacterium Treponema pallidum, it can be transmitted by sex, by parenteral and vertical pathways. Thus, the role of the dentist i salso essential, and you must be aware of the symptoms and orofacial signs that may appear in your office. Objective: to describe the epidemiological profile of syphilis in Brazil, to know its distribution according to the year of diagnosis and the gender of the patients, to verify the relationship between congenital syphilis and the mother's socioeconomic factors, adherence to prenatal care and to discuss the role of dentist against syphilis. Methods: Descriptive observational study, with data from DATASUS, related to acquired syphilis and congenital syphilis in the period 2014-2018. Results: The detection rate of acquired syphilis has increased over the years in the country; The percentage of acquired syphilis was higher in males in all years analyzed; In the period studied (2014-2018), the highest percentage of congenital syphilis occurred from mothers aged 20 to 29 years. Conclusion: Syphilis is a major public health problem, with a significant increase in notifications, even though there have been major advances in relation to prevention and treatment. Therefore, greater interest on the part of public policies is necessary for the creation of preventive and protective campaigns and health promotion, as well as a greater role for the dentist in the face of this problem.